Evaluation of Acute and Chronic Toxicity of Nickel and Zinc to 2 Sensitive Freshwater Benthic Invertebrates Using Refined Testing Methods. (16th September 2020) - Wang, Ning; Kunz, James L.; Cleveland, Danielle M.; Steevens, Jeffery A.; Hammer, Edward J.; Van Genderen, Eric; Ryan, Adam C.; Schlekat, Christian E.
Abstract: The US Environmental Protection Agency (USEPA) is reviewing the protectiveness of the national ambient water quality criteria (WQC) for nickel (Ni) and zinc (Zn) and compiling toxicity databases to update the WQC. An amphipod ( Hyalella azteca ) and a unionid mussel ( Lampsilis siliquoidea ) have shown high sensitivity to Ni and Zn in previous studies. However, there remained uncertainties regarding the influence of test duration (48 vs 96 h) and the presence and absence of food in acute exposures with the amphipod, and there were also concerns about poor control of amphipod growth and reproduction and mussel growth in chronic exposures. We conducted acute 48‐ and 96‐h water‐only toxicity tests to evaluate the influence of feeding and test durations on the toxicity of dissolved Ni and Zn to the amphipod; we also used recently refined test methods to conduct chronic Ni and Zn toxicity tests to evaluate the sensitivity of the amphipod (6‐wk exposure) and the mussel (4‐ and 12‐wk exposures). The 96‐h 50% effect concentrations (EC50s) of 916 µg Ni/L and 99 µg Zn/L from acute amphipod tests without feeding decreased from the 48‐h EC50s by 62 and 33%, respectively, whereas the 96‐h EC50s of 2732 µg Ni/L and 194 µg Zn/L from the tests with feeding decreased from the 48‐h EC50s by 10 and 26%, indicating that the presence or absence of food had apparent implications for the 96‐h EC50. Our chronic 6‐wk EC20s for the amphipod (4.5 µg Ni/L and 35 µg Zn/L) were 50 to 67% lower than the 6‐wk EC20s from previous amphipod tests, and our chronic 4‐wk EC20s for the mussel (41 µg Ni/L and 66 µg Zn/L) were similar to or up to 42% lower than the 4‐wk EC20s from previous mussel tests. The lower EC20s from the present study likely reflect more accurate estimates of inherent sensitivity to Ni and Zn due to the refined test conditions. Finally, increasing the chronic test duration from 4 to 12 wk substantially increased the toxicity of Zn to the mussel, whereas the 4‐ and 12‐wk Ni effect needs to be re‐evaluated to understand the large degree of variation in organism responses observed in the present study. Environ Toxicol Chem 2020;39:2256–2268. © 2020 SETAC